2015
DOI: 10.1371/journal.pone.0118703
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Analysis Identifies Indoxyl Sulfate as a Major, Poorly Dialyzable Uremic Toxin in End-Stage Renal Disease

Abstract: BackgroundChronic renal failure is characterized by progressive renal scarring and accelerated arteriosclerotic cardiovascular disease despite what is considered to be adequate hemodialysis or peritoneal dialysis. In rodents with reduced renal mass, renal scarring has been attributed to poorly filtered, small protein-bound molecules. The best studied of these is indoxyl sulfate (IS).MethodsWe have attempted to establish whether there are uremic toxins that are not effectively removed by hemodialysis. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…In hemodialysis [ 35 ] and in peritoneal dialysis [ 36 ] RRF was associated with better survival independent of the intensity of dialysis. Several studies have compared the concentrations of one or several uremic retention solutes in patients with RRF as compared with patients who are anuric [ 37 , 38 ]. In our small published study we reported that indoxyl sulfate concentration averaged 56 μmol/L in anuric patients and 37 μmol/L in subjects with RRF [ 37 ], a difference of about 33% which may be attributed to the secretion of uremic solutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hemodialysis [ 35 ] and in peritoneal dialysis [ 36 ] RRF was associated with better survival independent of the intensity of dialysis. Several studies have compared the concentrations of one or several uremic retention solutes in patients with RRF as compared with patients who are anuric [ 37 , 38 ]. In our small published study we reported that indoxyl sulfate concentration averaged 56 μmol/L in anuric patients and 37 μmol/L in subjects with RRF [ 37 ], a difference of about 33% which may be attributed to the secretion of uremic solutes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the concentrations of one or several uremic retention solutes in patients with RRF as compared with patients who are anuric [ 37 , 38 ]. In our small published study we reported that indoxyl sulfate concentration averaged 56 μmol/L in anuric patients and 37 μmol/L in subjects with RRF [ 37 ], a difference of about 33% which may be attributed to the secretion of uremic solutes. This difference in concentration provides one estimate of a difference that may account for the observed differences in clinical, largely cardiovascular, outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The level of IS in plasma is a significant predictor of major cardiac events [ 6 ], although other authors have found no association at all [ 7 ]. Regardless, a recent study identified IS as a major factor in the dysregulation of almost 2000 genes in vitro [ 8 ]. Moreover, poorly dialyzable uremic toxins are the leading cause of poor survival in dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…In effect, it may be that the patient with advanced or end-stage renal disease and RRF may excrete toxins in the same manner as the aglomerular anglerfish (33), namely by generating "urine" by tubular secretion rather than filtration. Jhawar et al (26), Klammt et al (28), and Marquez et al (37) have observed that plasma indoxyl sulfate concentration is greater in anuric patients than in patients who retain RRF. Analysis of large data sets suggest that patients with RRF, i.e., continued urine production while undergoing hemodialysis or peritoneal dialysis, have better "quality of life" and less cardiovascular disease than patients who are anuric (2,51).…”
mentioning
confidence: 98%
“…These data strongly suggest that factors other than GFR are more powerful determinants of uremic symptoms and outcome. These include renal tubular secretion of protein-bound uremic retention solutes (26,33,37,52), diet content of toxin precursors, toxin production by gut bacteria, and gut transit time (1,13,39,53,55). Furthermore, impaired proximal tubular secretion is now thought to contribute to the increased plasma levels of trimethylamine oxide (23,48,50) and tissue calcification (25), which may influence the outcome in patients with chronic renal disease.…”
mentioning
confidence: 99%